(untitled) - Lenk, John D. (Englewood Cliffs, New Jersey, 1968)
There is no scarcity of data on the subject of electronics. There are hundreds of books filled to the brim with basic theory and equa-tions. But this great variety, in itself, creates a problem. Where and how do you pin down specific information of a particular phase of electronics?
Keywords: Electronics,Điện tử